Sector scan of TUP enterprises: identifying determinants of sustainability - Alarakhia, Safeena; Barua, Proloy (BRAC, 2019)
A key objective of the CFPR-TUP programme to assist the ultra poor is the development of sustainable livelihoods, through the transfer of assets and skills to specially targeted ultra poor members for income generation. During the pilot phase of the programme between 2002-03, six enterprises were selected to offer to TUP members - cage rearing of poultry, dairy cow rearing, goat rearing, vegetable cultivation, horticulture nursery and non-farm enterprises. The sector scan of TUP enterprises is a comprehensive study comparing and evaluating the selected TUP enterprises on key criteria that relate to enterprise sustainability - the likelihood that TUP members will continue operating the enterprise after the withdrawal of BRAC programme support. The range of enterprises offered to TUP members differ in some important ways. These differences affect the ability of TUP members to sustain the enterprises, based on their individual, household and social circumstances. Enterprise specific characteristics such as risk and investment needs, and to a lesser extent time, skill and labour requirements are principle factors determining the likelihood of TUP members continuing with a given enterprise over the long term. Specifically, enterprises with combined characteristics of high risk and high investment costs, such as cage rearing of poultry and vegetable cultivation, were found to be sustainable by only a small percentage of TUP members who were initially allocated these enterprises. On the other hand, low risk enterprises, low cash investment enterprises such as cow rearing for which the main investment was time and labour, rather than cash, were found to be highly sustainable. Risk was found to be a key factor determining enterprise profitability. Projected enterprise economics, detailing expected costs and revenues and hence income available for consumption generated by TUP enterprises, typically overestimated profitability. The difference appears to be explained largely by enterprise related risks that occur in practice as TUP members operate their respective enterprises, and reduce profitability. External risks, outside the control of TUP members, such as weather and local market conditions, were found to be key risks in the agriculture based enterprises. In the case of livestock enterprises, internal risks, stemming from TUP actions, were found to be of primary importance. For example, a key factor constraining profits from cow and goat rearing was the inability of TUP to properly feed livestock due to a lack of access to grazing land reducing their value and output. Factoring in these risks changes the picture of the income TUP enterprises are likely to generate and their relative attractiveness as ongoing sources of income...